1999
DOI: 10.1540/jsmr.35.55
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Studies of the Effect of Dai-kenchu-to on Spontaneous Contraction of Isolated Rabbit Jejunum.

Abstract: We studied the effects of Dai-kenchu-to on the spontaneous contraction in isolated rabbit jejunum. Dai-kenchu-to (10-3g/ml) increased jejunal contraction, such as phasicchu-to and Zanthoxyli Fructus reversed the decrease of contraction produced by atropine.However, phasic-like contraction induced in the absence of atropine was antagonized by atropine. Dai-kenchu-to and Zingiberis Siccatum Rhizoma further decreased spontaneous contraction in the presence of tetrodotoxin.It was clarified that Dai-kenchu-to posse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 9 publications
2
30
0
Order By: Relevance
“…In animal experiments, DKT increases dog intestinal motility in vivo (Furukawa et al, 1995). DKT evokes contractions in isolated intestine of rabbit and guinea pig (Kurosawa et al, 1998;Hayakawa et al, 1999b;Satoh et al, 2001aSatoh et al, , 2001b. In contrast, DKT inhibits carbachol induced contraction in rat colon (Tulimat et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In animal experiments, DKT increases dog intestinal motility in vivo (Furukawa et al, 1995). DKT evokes contractions in isolated intestine of rabbit and guinea pig (Kurosawa et al, 1998;Hayakawa et al, 1999b;Satoh et al, 2001aSatoh et al, , 2001b. In contrast, DKT inhibits carbachol induced contraction in rat colon (Tulimat et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Zanthoxylum fruit contracted smooth muscle preparations of rabbit jejunum and guinea pig ileum through ACh release (Kurosawa et al, 1998;Hayakawa et al, 1999b;Satoh et al, 2001a). On the other hand dried ginger root relaxed rabbit jejunum (Hayakawa et al, 1999b). Therefore multiple actions of DKT may be produced as a result of mixture of these herbs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 In experiments with isolated intestines, DKT induced contractions in rabbit jejunum and guinea pig ileum and colon. 4,5 DKT administered directly into the stomach caused phasic contractions through cholinergic and 5-hydroxytryptamine 3 (5-HT 3 ) receptors in the gastric antrum, duodenum, and jejunum in dogs. 1 In isolated guinea pig ileum, hydroxy β-sanshool, one of the ingredients of DKT, induced contractions through the release of acetylcholine from intrinsic cholinergic nerves and tachykinins from sensory neurons.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] We confirmed that the administration of Dai-kenchu-to causes significant increases in the levels of motilin, vasoactive intestinal polypeptide (VIP), serotonin, calcitonin gene-related peptide (CGRP), and substance P in human plasma. [5][6][7] These results indicate that the gastrointestinal motor activity of Dai-kenchu-to is closely related to changes in these neuropeptides in human plasma.…”
mentioning
confidence: 60%